Analisis Permintaan Pasar Telur Ayam Di Provinsi Sumatera Barat - Jum'atri Yusri; . Andri; E. Syahputra (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2007)
The research was objected to study the market demand on egg in West Sumatra in retain to several defined factors, i.e.: population number, people income, price of egg, broiler meat, beef meat, fish, rice and wheat flour. Secondary data were collected from 1985-2004 and statistically analyzed by using econometrics approach. Results showed that market demand of chicken egg in Sumatra Barat was significantly affected by the price of the egg and broiler meat and beef meat. The increase of population and their income gave no significant effect on egg demand.